POLA KOMUNIKASI ORANG TUA DAN REMAJA DALAM KELUARGA DI RT IV RW XV KELURAHAN MATA AIR KECAMATAN PADANG SELATAN - Ricardo, Kiki; Syarif, Mellyarti; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
This study aimed to describe the pattern of parent and adolescent communication in families at RT IV Fountain District Urban Village South Padang, with the aim of the study is 1). Stimulus-response model describes the pattern of parental communication with adolescents in the family and 2). Interactional models to describe the patterns of parent-adolescent communication in families at RT IV Fountain District Urban Village South Padang. This research is a descriptive study. Researchers took the study population was elderly and adolescents. This study uses total sampling technique. Analysis of the data used is to create a table for each variable and cross tables and bar charts among variables to describe patterns of parent-adolescent communication in families. Data analysis using the percentage formula. Results of research conducted can be described as follows: 1) The application of the communication patterns of parents and adolescents in families with stimulus-response models included in both categories with a percentage of 56%, 2) Application of communication patterns of parents and adolescents in families with Interactional models included into categories with a percentage of 62%, 3) Application of communication patterns teens and parents in families with stimulus-response models included in both categories with a percentage of 61% and 4) Application of communication patterns teens and parents in families with Interactional models included in both categories with a percentage of 60%. The author suggests that parents of adolescent communication should run well, parents should use gentle words in communicating with teens to avoid things that are not desirable, and vice versa teens want to show good communication to parents.Â